source : edustrings.com

## If f (x) = 4

Find an answer to your question ✅ “If f (x) = 4 – x2 and g (x) = 6x, which expression is equivalent to (9-1 (3) ? …” in 📘 Mathematics if you’re in doubt about the correctness of the answers or there’s no answer, then try to use the smart search and find answers to the similar questions.

Search for Other Answers

If f(x) = 4 – x2 and g(x) = 6x, which expression is – #(g-f)(x)=g(x)-f(x)# #color(white)(xxxxxx)=6x-(4-x^2)# #color(white)(xxxxxx)=x^2+6x-4# #"to evaluate "(g-f)(3)" substitute x = 3 into "(g-f)(x)# #(g-f)=(color(red)(3Graph f(x)=x^2-4. Find the properties of the given parabola. Tap for more steps… Rewrite the equation in vertex form. Tap for more steps… Complete the square for . Replace the variable with in the expression. Simplify the result. Tap for more steps… One to any power is one. Subtract from . The final answer is . The value at is .if f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (g – f)(3)? a: 6 – 3 – (4 3)2 b: 6 – 3 – (4 – 32) c: 6(3) – 4 32 d:6(3) – 4 – 32 – 1689554

Graph f(x)=x^2-4 | Mathway – x^2-x-6=0; x^4-5x^2+4=0 \sqrt{x-1}-x=-7 \left|3x+1\right|=4 \log _2(x+1)=\log _3(27) 3^x=9^{x+5} equation-calculator. f(g(2)), g(x)=2x+1, f(x)=x^{2} en. Related Symbolab blog posts. Middle School Math Solutions – Equation Calculator. Welcome to our new "Getting Started" math solutions series. Over the next few weeks, we'll be showing howPlay this game to review Algebra I. At a restaurant jars of tomato sauce are stored in boxes in the pantry. Each box contains 8 jars of tomato sauce. A cook uses 2 jars from 1 of the boxes. Which function shows the relationship between y , the total number of jars of tomato sauce remaining in the pantry, and x >, the number of boxes in the pantry?</p>Solve your math problems using our free math solver with step-by-step solutions. Our math solver supports basic math, pre-algebra, algebra, trigonometry, calculus and more.

if f(x) = 4 – x2 and g(x) = 6x, which expression is – Q1. Which expression is equal to (f o g)(x)? f(x)=x^2+3; g(x)=6x A. 36x^2+18 B. 6x^3 + 18x C. 36x^2 + 3 D. 6x^2+3 My answer is B I think. Q2. Use the function f(x) and g(x) to answer the question. f(x)=4x-5; g(x)=x+3 Which expression is equal to (g o f)(x)? A. 4x+7 B. 5x-2 C. 4x + 12 D. 4x-2 My answer is C I think Q3. Which is the value of (f o g)(-5) f(x)=2x+1;g(x)=x^2 A. -19 B. 51 C. 11 Df(x) = something with "x" g(x) = something else with "x" as the variable. Think of a function as a recipe. "f" is the name of one recipe. "x" is the secret ingredient and everything after the equal sign is the recipe (the instructions on what to do with the secret ingredient, once you are told what it is).1. Introduction The composition of two functions g and f is the new function we get by performing f ﬁrst, and then performing g. For example, if we let f be the function given by f(x) = x2 and let g be the function given by g(x) = x+3, then the composition of g with f is called gf and is worked out